Genotypic profiling of methicillin resistance and virulence in MRSA: Subtyping of SCCmec type I to V and PVL genes in clinical isolates from tertiary care hospital - Vivekanand Jadhav; Sanjo Gupta; Arundhuti Paul; Rahul Bhalsinge; Savita V Jadhav (Journal of Krishna Institute of Medical Sciences University, 2025)
Background: Methicillin-Resistant Staphylococcus Aureus (MRSA) remains a significant cause of healthcare- and community-associated infections. Molecular characterisation of resistance and virulence determinants is essential to understand its evolving epidemiology. Material and Methods: A total of 153 MRSA isolates from a tertiary care hospital were categorised as Community-Acquired (CA-MRSA, 63.3%) or Hospital-Acquired (HA-MRSA, 36.6%) based on clinical criteria. Methicillin resistance was confirmed by cefoxitin disk diffusion. Multiplex PCR was performed for SCCmec (types I–V) and Panton-Valentine Leukocidin (PVL) gene detection. Non-typable isolates (n= 21) underwent additional PCR assays. Results: All CA-MRSA isolates harboured mecA and PVL genes. Among HA-MRSA isolates, 16% were PVL-positive, including 1.3% PVL-positive/mecA-negative strains suggestive of PVL-positive MSSA. SCCmec type IVa was predominant (73.5%). Non-typable isolates exhibited high genetic variability. Conclusion: The co-occurrence of mecA and PVL genes and detection of PVL in HA-MRSA suggest blurring epidemiological boundaries between CA-MRSA and HA-MRSA. The findings highlight the importance of molecular surveillance and complementary genotyping methods to inform public health interventions against multidrug-resistant MRSA.